CALENDAR FOR PLANTING SEAWEED EUCHEUMA SP. IN MALLASORO BAY, JENEPONTO DISTRICT, BASED ON LANDSAT-8 IMAGES - Amran, Muhammad Anshar; Niartiningsih, Andi; Faizal, Ahmad; Rasyid, Abdul; Muhiddin, Amir Hamzah; Arifin, Isnaeni (Jurnal Ilmu Kelautan SPERMONDE, 2023)
Seaweed cultivation activities in Jeneponto Regency have been practised for a long time and have become the main livelihood for most of the Mallasoro Bay community. In cultivating seaweed, obstacles often arise in the form of failures experienced by seaweed farmers or poor-quality yields. This study was aimed to develop alternative planting calendars for Eucheuma sp. in Mallasoro Bay, Jeneponto Regency based on sea surface temperature and distribution of chlorophyll-a obtained from Landsat-8 imagery. Image Processing Sea Surface Temperature and Chlorophyll-a were processed using ENVI 4.8 AND 5.3 software, the satellite images used were clean and without cloud disturbance. In this study, data analysis was carried out descriptively. The water temperature that is good for seaweed growth is 27-30˚C, for Mallasoro Bay Sea Surface Temperature which is suitable for seaweed cultivation, namely April, May, June, July, August, September, October and November. While the classification is based on the criteria for chlorophyll-a trophic status in marine waters, namely the range < 1 mg/L is classified as Oligotrophic, ≥ 1–3 mg/L is classified as Mesotrophic, ≥ 3–5 mg/L is classified as Eutrophic, and > 5 mg/L is classified as Hypertrophic. , from the results of image analysis for the distribution of chlorophyll-a in Mallasoro Bay, it shows that Mallasoro Bay is at the Mesotrophic level throughout the year or the fertility level of the waters is quite fertile because it is in the range of ≥ 1–3 mg/L. so that a seaweed planting calendar can be obtained in Mallasoro Bay, namely in January, February and December, preparation of tools such as cleaning and repair of seaweed planting tools can be carried out, then at the end of March, the end of May, the end of July and the end of September, the procurement of seaweed seeds is carried out. , in early April, early June, early August, and early October, seaweed seeds can be spread, then in mid-May, mid-July, mid-September, and mid-November, harvesting can be carried out, so that seaweed cultivation can be carried out 4 times in one year. cycle.